2014
DOI: 10.1007/s00774-014-0601-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the in vitro mineralisation and dentinogenic potential of mesenchymal stem cells derived from adipose tissue, bone marrow and dental pulp

Abstract: Stem-cell-based therapies provide a biological basis for the regeneration of mineralised tissues. Stem cells isolated from adipose tissue (ADSCs), bone marrow (BMSCs) and dental pulp (DPSCs) have the capacity to form mineralised tissue. However, studies comparing the capacity of ADSCs with BMSCs and DPSCs for mineralised tissue engineering are lacking, and their ability to regenerate dental tissues has not been fully explored. Characterisation of the cells using fluorescence-activated cell sorting and semi-qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 63 publications
2
82
0
6
Order By: Relevance
“…DT ¼ CT=doubling numberðnf ¼ final number of cells at 80% confluence; ni ¼ initial number of cells; and CT ¼ culture timeÞ (2) Karyotyping Post-thaw P4-HDPCs were exposed for 3 hours to 0.7% colcemid (Life Technologies) diluted in the culture medium, and then cells were detached and centrifuged. The pellet was then resuspended in 0.075 mol/L KCl for 2 minutes at room temperature.…”
Section: Cell Viability Cumulative Doubling Number and Doubling Timmentioning
confidence: 99%
See 1 more Smart Citation
“…DT ¼ CT=doubling numberðnf ¼ final number of cells at 80% confluence; ni ¼ initial number of cells; and CT ¼ culture timeÞ (2) Karyotyping Post-thaw P4-HDPCs were exposed for 3 hours to 0.7% colcemid (Life Technologies) diluted in the culture medium, and then cells were detached and centrifuged. The pellet was then resuspended in 0.075 mol/L KCl for 2 minutes at room temperature.…”
Section: Cell Viability Cumulative Doubling Number and Doubling Timmentioning
confidence: 99%
“…In this context, stem/progenitor cells appear to be particularly appropriate because of their high expansion ability and differentiation potential both in vitro and in vivo (1). If bone marrow and adipose tissue are considered potential sources of stem/progenitor cells, painful collection protocols, the decline of the amount of stem/ progenitor cells with age, the necessity of general anesthesia, reduced proliferation capacity, and risk of morbidity at the collection site encourage the search for alternative candidates (1,2). Human impacted third molars are frequently removed for therapeutic reasons and the loose connective tissue they contain; the dental pulp appears to be a valuable source of stem/progenitor cells for pulp/dentin and bone engineering.…”
mentioning
confidence: 98%
“…Various studies have widely demonstrated the ability of adipose-derived stem cells (ADSCs) to differentiate into mesenchymal-derived cell lines (adipocytes, osteoblasts, chondroblasts, and endothelial cells) and not mesenchymal cell lines (skeletal muscle cells, cardiac cells, and neuronal cells) (12)(13)(14)(15). Numerous papers have been published in recent years on bone regeneration for skeletal and mandibular repair using ADSCs (16)(17)(18) …”
Section: Introductionmentioning
confidence: 99%
“…DPSCs have shown the greatest potential to produce a high volume of mineralized matrix, suggesting that these cells also show promise for use in regenerative dental therapies. 28 Dental pulp progenitors have not been clearly identified but some data suggest that pericytes, which are able to differentiate into osteoblasts, could also differentiate into odontoblasts. 29 …”
Section: Dscmentioning
confidence: 99%